Effect of feeding bypass fat on production, reproduction, feed and economic efficiency of dairy cows - LUNAGARIYA, PRAVIN M; V SHAH, SHAILESH; G PATEL, YOGESH; N WADHWANI, KISHAN (The Indian Journal of Animal Sciences, 2022)
The dairy cows experience negative energy balance during early lactation and feeding Bypass fat in ration can produce higher milk yield, improved reproduction with better economics. An experiment was planned to evaluate feeding of total mixed ration (TMR) supplemented with Bypass fat @ 100 g/day to dairy animals for -21 to 120 days of calving. Total sixteen animals were divided to control and Bypass fat group having eight animals in each. The effect on production, reproduction and economics was evaluated for 21 biweekly periods and for 300 days of lactation. The feeding total mix ration (TMR) supplemented with 100g/day Bypass fat (98%; -21 to 120 days of calving) was resulted in daily 1.19 kg higher (p=0.050) residual whole milk, 1.21 kg daily higher (p=0.048) residual 4% FCM yield whereas improvement in whole milk, 4% fat corrected milk yield and milking days (25 days) was numerical for period of 1-21 bi-week period. An intake of dry matter and nutrient was non-significant between the groups. The better feed conversion ratio (kg/kg milk) in terms of dry matter (1.581±0.11 vs. 2.330±0.39; p=0.048) and total digestible nutrients (0.846±0.06 vs. 1.300±0.21 kg; p=0.046), improved reproduction in terms of Artificial insemination (AI)/conception (1.857±0.14 vs. 2.286±0.18; p=0.008) and service period (113.13±20.73 vs. 177.38±20.92 days; p=0.014) and better feed cost to milk income ratio (1:1.93 vs. 1:1.63) in lactating cows during standard lactation. The lower loss of body condition score of bypass fat group cows after calving resulted in better milk yield and reproduction of dairy cows.